Assessing resistance and bioremediation ability of enterobacter sp. Strain saw-1 on molybdenum in various heavy metals and pesticides - Sabullah M.K.; Rahman M.F.; Ahmad S.A.; Sulaiman M.R.; Shukor M.S.; Shamaan N.A.; Shukor M.Y. (Institute for Research and Community Services, Institut Teknologi Bandung, 2024)
Index by Scopus & WOS